2016
DOI: 10.26848/rbgf.v9.2.p413-429
|View full text |Cite
|
Sign up to set email alerts
|

Influência das Variáveis Climáticas na Hospitalização por Pneumonia em Crianças Menores de Cinco Anos em Rondonópolis-MT (Influence of Variable Climate in Hospital for Pneumonia in Children Under Five Years in Rondonópolis-MT)

Abstract: As infecções respiratórias agudas constituem o principal motivo de consulta e hospitalização de crianças menores de cinco anos, sendo a pneumonia uma das principais causas de morte. O objetivo desta pesquisa foi analisar a influência das variáveis climáticas na hospitalização por pneumonia em crianças menores de cinco anos em Rondonópolis-MT, no período de 1999 a 2014. Estudo do tipo transversal com abordagem quantitativa e descritiva, com dados do banco de dados meteorológicos para ensino e pesquisa e do depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…59 Other studies have observed the same association. 60,61 With regard to climatic conditions, studies by Natalli et al 62 and Santos et al 63 identified a higher proportion of hospitalization for pneumonia in periods with the first cold fronts that cause sudden changes in temperatures, a fact that corroborates our study, in which one of the most affected regions was the south, which is considered the coldest in Brazil and also has one of the highest concentrations of industry, which may be related to the highest concentration of air pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…59 Other studies have observed the same association. 60,61 With regard to climatic conditions, studies by Natalli et al 62 and Santos et al 63 identified a higher proportion of hospitalization for pneumonia in periods with the first cold fronts that cause sudden changes in temperatures, a fact that corroborates our study, in which one of the most affected regions was the south, which is considered the coldest in Brazil and also has one of the highest concentrations of industry, which may be related to the highest concentration of air pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high humidity explained 84% of the hospitalizations. 23 Regarding the frequency of hospitalization in different seasonal periods, Santos et al 24 investigated the population aged 0 to 5 years in the city of Rondonópolis, Brazil. They reported that there were greater numbers of hospitalizations due to pneumonia in the months of April and May.…”
Section: Discussionmentioning
confidence: 99%